BONUM COMMUNE DALAM BINGKAI KEBANGSAAN: PERJUANGAN PARTAI POLITIK - Petrus Canisius Edi Laksito (Arete, 2019)
AbstractTo speak of bonum commune from the standpoint of the tradition of the In- donesian Catholic Church, this paper does not emphasize the theories of thinkers or their leaders. The priority is precisely the “struggle practices” of the Catholics seeking “conditions of inner and outer well-being” for each individual citizen and community groups in the life of the Indonesian nation. From there it is hoped that the relevance of the idea of bonum commune can be found and its significance for living together. At the pragmatic level, the benchmarks are of course the fruits for the Indonesian people. Normatively, ideologically, the measure is its compatibility with the principles of nation and state, namely Pancasila and Bhinneka Tung- gal Ika. In order for the discussion to be on its track to understand the bonum commune according to Church doctrine, a few items of understanding from the Church's oßcial sources were previously presented.This study was directed at the first period of the Catholic Party's journey, covering the period from its establishment until the recognition of the sovereignty of the Republic of Indonesia by the Dutch Government on December 27, 1949. The recognition it self was the final result of the Round Table Conference (Ronde Tafel Conferentie), namely a meeting between the Netherlands and Indonesia in The Hague, the Netherlands on August 23 to November 2, 1949. The two periods after that, namely the period of liberal democracy and guided democracy as well as the initial period of the New Order to fusion into the Indonesian Democratic Party, are expected to be discussed in other opportunities . Keywords: Catholic, Indonesia, Bonum Commue